Attaining Financial Inclusion through Ijarah Contract: Assessing the Potentials of Ijarah-Wa-Iqtina in Venture Financing of Tricycles in Kano Metropolis, Kano State, Nigeria - Bako, Muhammad; Aliyu, Shehu U. R. (International Journal of Islamic Business & Management, 2018)
Ijarah-wa-iqtina, also known as Al-Ijarah Thummal Al-Bay (AITAB) is a leasing contract where the ownership of the leased asset is transferred to the lessee at the end of the leasing contract. With the inception of Ja’iz Bank Nigeria Plc, the product has grown in the Ja’iz Bank’s housing and auto-finance. Despite this popularity, majority of small scale businesses especially tricycle operators in Kano metropolis are still not aware of the product and the benefits attached to it. This research assesses the potentials of Ijarah-wa-iqtina in financing tricycle operation in Kano using a multiple regression model from a sample of 311 respondents. The study found myriad of problems associated with conventional mode financing arrangements prior to ijarah-wa-iqtina. It was also established that religious inclinations of respondents have strong influence on potential benefits from switching to ijarah-wa-iqtina. The paper recommends that Islamic financial institutions and well-to-do business persons in Kano metropolis on the need to promote both formal and non-formal Islamic finance among tricycles operators via ijarah-wa-iqtina.